Compassion-Driven Innovation 12 Steps for Breakthrough Success - Reineke, Nicole; Reineke, Nicole; Yehuda, Hanna (Business Expert Press, 2022)
This book is for pathfinders$1 (Bproduct, services, business, and nonprofit managers searching for ways to reach beyond the artificial barriers that constrain innovation and make (3z(Bwork(3y (Bharder.Inspired by real life trailblazers and their own experiences, the authors decode the secrets of achieving breakthrough success at both organizational and interpersonal levels. Learn to use their methodology with the help of checklists and detailed examples that will transform your thinking and skills.s